Properties of Specialist Fibres and Bragg Gratings for Optical Fiber Sensors. (21st July 2009) - Canning, John
Abstract : The advent of optical fibres based on air holes running along their entirety opens up new directions in addressing various properties relevant to sensing, including the temperature/strain challenge of optical fibre sensors. This paper looks at the measurement challenges associated with temperature and strain, examines the potentially unique functionality structured fibre designs with and without gratings open up, and briefly describes some current research directions within conventional fibre and grating technologies.